Analysis Of The Utilization Of Mindmeister Visual Organizer Application In Building Students' Critical Thinking In Islamic Religious Education Learning - Dwi, Dwi Susanti; Diah Puspaningrum; Bakti Fatwa Anbiya (Journal of Teacher Training and Educational Research, 2023)
This study aims to evaluate MindMeister, a visual organizer app, in the context of learning Islamic Religious Education. Through a qualitative approach with a literature study method, this research analyzes the app in helping students strengthen critical thinking. Data from books and relevant scientific articles were collected and analyzed using the Miles and Huberman model. The results show that the utilization of MindMeister positively influences students' critical thinking, improving the effectiveness and efficiency of Islamic Religious Education learning. Data validation was conducted through triangulation to ensure the completeness and validity of the information. This study can serve as an important foundation in developing ways to utilize MindMeister to enrich Islamic Religion learning as well as improve students' critical thinking.